Sistem Informasi Pelaksanaan KKN Berbasis Web di Universitas Negeri Makassar - Muh. Alwi Rizkyansyah Kasim; Muhammad Agung; Jumadi Mabe Parenreng; Mustari S. Lamada; Abdul Wahid (Progressive Information, Security, Computer, and Embedded System, 2024)
The research conducted is Research and Development (R&D). The aim of this study is to determine the results of the development of a web-based Community Service Program Implementation Information System using the prototyping development method. Additionally, the research aims to assess the quality of the developed software using the ISO 25010 standard. The data collection techniques used include questionnaires, interviews, observations, and documentation. This study resulted in a web-based Community Service Program Implementation Information System using the Laravel framework. The testing results indicated good quality, detailed across eight aspects: functional suitability scored 0.956 and 0.978 from the two functionality testers, both of which are categorized as "good"; usability received a score of 90.76%, categorized as "very feasible"; performance efficiency was graded A, indicating good quality; reliability showed a 99.93% score, categorized as good; security testing revealed level 1 vulnerability to password guessing attacks, while tests for SQL injection and cross-site scripting indicated that the system is secure from these attacks, overall indicating good security quality; maintainability scored 0.027 with an A grade from SonarQube tools, categorized as good; portability showed good quality after testing on four different operating systems and two different hardware types; and compatibility showed good quality after testing on five different browsers.